Desalination and power generation of caspian sea by applying new designed microbial desalination cells in batch operation mode. Issue 5 (2nd April 2019) - R. Kalankesh, Laleh; Rodríguez‐Couto, Susana; Zazouli, Mohammad Ali
Abstract : The Caspian Sea is one of the largest water sources located in the north of Iran; so this research was carried out to investigate the new design of microbial desalination cell (MDC) (double layer) efficiency in water desalination and power generation of the enormous saline water source in the north of Iran. Actual (i.e., Caspian Sea) and artificial seawater with different initial salt concentrations (5, 25, and 35 g/L NaCl) and, different hydraulic retention times (24, 48, and 72 h) in batch and open circuit voltage (OCV) mode were examined. In addition, the oxidation and reduction processes during desalination of each stage were monitored at 10 min intervals for 60 min. According to the obtained experimental data, both the desalination efficiency and the power generation decreased from 65 ± 1% to 41 ± 1% and 80 ± 4.5 mW/cm2 to 51.20 ± 2.5 mW/cm2 by increasing the retention time from 24 to 72 h for Caspian Sea water and 5 g/L NaCl, respectively. Maximum and minimum desalination efficiencies were 48 ± 1% and 65 ± 1% for Caspian Sea water and 5 g/L NaCl, respectively. Moreover, the maximum power densities were 72.83 ± 3.36 mW/cm2 and 80.00 ± 4.00 mW/cm2 for 35 g/L NaCl and seawater, respectively. As far as the authors know, this is the first study on the application of the new designed stacked MDC for power generation and desalination of water from the Caspian Sea. © 2019 American Institute of Chemical Engineers Environ Prog, 38:e13146, 2019